1988
DOI: 10.1210/endo-123-6-2626
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Inhibition of Luteinizing Hormone Release Declines with Age and Acyclicity in Female Rats*

Abstract: The current study assesses changes in opioid inhibition of LH secretion with age in female rats. We administered naloxone (NAL; 2 mg/kg, iv) to regularly cycling estrous rats of three age groups and measured serum LH in serial samples drawn from intraatrial catheters before and after treatment. The serum LH rise 10 min after NAL treatment in 4- to 6-month-old rats was significantly reduced (P less than 0.01) compared with that in 1.5- to 3-month-old animals, and no LH response was observed in 8- to 11-month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…That is, although the shortest interval produced by naloxone was about 6 min in both rats, the period of the effect was shorter in old ovariectomized rats, as seen in figure 5. This may mean that in these extremely old rats a certain number of opioid neurons and/or opioid receptors are still involved in the tonic inhibition of the activity of the GnRH pulse generator, but they are significantly fewer than those in young rats, as suggested previously [25, 28, 40]. In support of this, the decrease in POMC mRNA levels in the hypothalamus has been reported in old-aged mice [41]and rats [42].…”
Section: Discussionsupporting
confidence: 58%
“…That is, although the shortest interval produced by naloxone was about 6 min in both rats, the period of the effect was shorter in old ovariectomized rats, as seen in figure 5. This may mean that in these extremely old rats a certain number of opioid neurons and/or opioid receptors are still involved in the tonic inhibition of the activity of the GnRH pulse generator, but they are significantly fewer than those in young rats, as suggested previously [25, 28, 40]. In support of this, the decrease in POMC mRNA levels in the hypothalamus has been reported in old-aged mice [41]and rats [42].…”
Section: Discussionsupporting
confidence: 58%
“…A recent report has suggested age-related de clines in the content of opiate receptors in some brain areas [30], Further, age-related declines in opioid inhibition of LH have been reported in intact rats of both sexes [31,32[. In female rats [31], the LH increase after naloxone treatment in 4-to 6-month-old rats was significantly reduced compared with that in 1.5-to 3-month-old rats, and no LH response was ob served in 8-to 11-month-old rats, which results were inter preted as suggestive of age-related declines in opioid neuronal activity or receptor numbers. Considering the age at which our rats were OVX in the present study, 32-week OVX rats were 10 months old, so that it is plausible that such a hypothesis is ap plicable to the results of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…GnRH release, also elicits a greater release of LH from young than from middle-aged females [28,29], although Wise et al [12] found no difference in LH concentration or pulse frequency between young and middle-aged ovariectomized rats given naloxone. Some of the decrease in pituitary responsiveness to GnRH may be the result of reduced pituitary GnRH receptors: middle-aged rats have fewer GnRH receptors during diestrus, and they show an attenuated increase in receptors in response to electrical stimulation of the medial preoptic area compared to young rats [30].…”
Section: Discussionmentioning
confidence: 99%